Assessing the impact of appendicectomy in daily activities/social life of children - Srinivasan K,; Divakar Pandian, (Asian Journal of Medical Sciences, 2024)
Background: Appendicectomy is a common surgical procedure for children presenting with appendicitis. Understanding the impact of appendicectomy on daily activities and social life is crucial for optimizing patient outcomes. Aims and Objectives: This study aimed to assess the impact of appendicectomy on children’s daily activities and social lives. Materials and Methods: A retrospective analysis was conducted of patients aged ≥5 years who underwent appendicectomy at our center between April 2022 and April 2023. Data on demographics, surgical approach (open or laparoscopic), post-operative outcomes, and return to daily activities were collected using a standardized questionnaire. Results: Among the 70 identified cases, there was a male predominance (63%), with most presenting with acute appendicitis (85%). Laparoscopic appendectomy was the predominant surgical approach used (80%). Post-operative symptoms included pain (n=12), vomiting (n=3), fever (n=2), and wound infection (n=6). Appendicular abscesses were found in 9% of laparoscopic surgeries and 14% of open surgeries. The average duration of hospital stay was shorter in laparoscopic cases. Return to school and normal diet varied between surgical approaches, with laparoscopic cases generally showing a quicker recovery. Conclusion: Although appendicectomy is commonly performed, it has implications for children’s daily routines and social interactions. Parental anxiety plays a crucial role in post-operative recovery. Future studies should focus on addressing these social determinants to optimize patient outcomes.